REGULATORY CHALLENGES IN RURAL WASTE MANAGEMENT: BETWEEN POLICY AND COMMUNITY COMPLIANCE (Case Study in Wanasaba Lor Village) - Alko Priadinata; Puput Indriani; Muhamad Frananda; Dea Kania Putri; Ratu Mawar Kartina (Jurnal Abdisci, 2025)
The issue of waste management in Wanasaba Lor Village reflects the low level of community compliance with environmental policies set by the village government. The provision of waste transportation facilities has not received optimal support from residents, who prefer to burn their waste, resulting in air pollution and contradicting applicable environmental regulations. This study employs a normative juridical method with a statutory and conceptual approach to analyze the effectiveness of waste management regulations and the implementation of good governance principles in village-level environmental policies. The study results indicate that low community compliance is caused by several factors, including waste fee burdens, lack of environmental awareness, and minimal supervision and law enforcement. To address this issue, more effective legal strategies are needed, such as the formulation of Village Regulations (Perdes) prohibiting waste burning, strengthening legal culture-based education and outreach, and implementing incentive and disincentive systems to encourage community compliance. The implementation of these strategies has been proven successful in other regions, such as Sidokerto Village, Raksasari Village, and Yogyakarta City, which have enforced strict regulations, environmental education, and incentive schemes in waste management. By adopting these measures, it is hoped that Wanasaba Lor Village can enhance waste management effectiveness and encourage greater community responsibility for environmental sustainability. The good governance principles, which emphasize participation, transparency, and accountability in public policy, are the key to establishing a sustainable waste management system.